Meta-Analysis of the Effectiveness of Teledentistry on Patients Satisfaction - Utsani, Wimmy Safaati; Demartoto, Argyo; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Preventive strategies of caries prevention, such as topical fluoridation or drinking water, have been effective in inhibiting the development of carious lesions. Teledentistry is an alternative service that combines dentistry with long-distance telecommunication technology for consultation and treatment planning that can be used for dental and oral health education to increase public awareness. The purpose of this study was to analyze the effectiveness of teledentistry on patient satisfaction. Subjects and Method: This study was a meta-analysis with the following PICO, population: patients. Intervention: teledentistry. Comparison: conventional (outpatient). Outcome: patients satisfaction. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles are “teledentistry” OR “oral hygiene” AND “multimedia” OR “smartphone app” OR “online social media” AND “patient satisfaction”. The articles included are full text English with a randomized control trial study design from 2013 to 2023. The selection of articles was carried out using the PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application. Results: A total of 9 case studies from the continents of Europe (Netherlands, Germany, Italy), North America (Pennsylvania), and Asia (India, Saudi Arabia, Iran) were selected for systematic review and meta-analysis. The results showed that 1.05 units of teledentistry increased patient satisfaction compared to not being given teledentistry. Statistical results (SMD = 1.05; 95% CI= 0.64 to 1.46; p < 0.001). Conclusion: Teledentistry increased patient satisfaction Keywords: teledentistry, oral hygiene, online social media, patients satisfaction Correspondence: Wimmy Safaati Utsani. Masters of Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: wimmysafaatiutsani@gmail.com. Mobile: +6285725333556